Evaluation of Viscosity of Traditional Medicinal Antihyperglycemic Plant Extracts and Relationship with Glucose Diffusion In vitro - F Asgharpour; M Pouramir; AA Moghadamnia (Institue of Medicinal Plants, ACECR, 2012)
Background: One of the mechanisms in reducing blood glucose is preventing the digestive absorbtion of glucose.   Objective: The aim of this study was to investigate the viscosity and impact some plants useful in reducing the glucose and their effects on decreased glucose movmentvia via dialysis bag in vitro.   Methods: Eleven traditional antihyperglycemic plants Liquid extracts were prepared after confirmation. The viscosity of the plant extracts was measured using viscometer. Different concentration (6.25, 12.5, 25, 50 g/l) of the extracts were addad to dialysis bag content D - glucose 0.22 M. Dialysis bag having only D - glucose 0.22 M was considered as control. The Liquid glucose concentration out of dialysis bag in room temperature was measured in time interval during 24 hours using the glucose oxidase method. The area under the glucose curve (AUC) was calculated using trapezium rule and AUC of different groups were compared.   Results: Highest viscosity was belonging to Pyrus biosseriana 50 g/l (1.69 mpas) and Securigera securidaca (1.46 mpas). Decreased glucose movment from dialysis bag considering AUC was related to extracts of 50 g/l of Eucalyptus globulues (% 82) . Decreased glucose movment were extract concentration dependent but in the each extract concentration decreased glucose movement was less than control. Conclusion: The extracts of the traditional antihyperglycemic plants reduce the glucose diffusion in laboratory model. It seem that viscosity is effective in the decrease glucose movment, but this was not observed in case of Eucalyptus globulues extract, that probably another reason has a role in this relation.